Harlequin Ichthyosis in a Preterm Neonate Born to a Consanguineous Couple: A Case Report and Prenatal Diagnostic Challenges - Jaiswal, Parul; Patvekar, Meenal; Jagtap, Akshay (Journal of Neonatal Surgery, 2025)
Harlequin ichthyosis (HI) is a rare, severe autosomal recessive disorder affecting the epidermal barrier due to ABCA12 gene mutations. It presents with thick, hyperkeratotic skin, severe ectropion, eclabium, and limb deformities, often leading to perinatal complications. This case report describes a 19-year-old unregistered primigravida at 35 weeks of gestation with a history of consanguineous marriage, presenting with preterm premature rupture of membranes (PPROM) and obstetric pain. A vaginally delivered female neonate weighing 2.2 kg exhibited classical HI features, including fissured skin, underdeveloped auricles, cyanosis, and bradycardia. Despite advances in prenatal imaging, early detection remains challenging, particularly in resource-limited settings. Ultrasound findings such as thickened skin, fetal akinesia, and polyhydramnios can suggest HI, but definitive molecular diagnosis via amniocentesis or chorionic villus sampling is not widely accessible. Maternal risks include polyhydramnios, preterm labor, and increased cesarean delivery rates, requiring vigilant antenatal monitoring. Genetic counseling is critical for affected families, emphasizing the 25% recurrence risk in future pregnancies. This report underscores the need for enhanced prenatal screening protocols and multidisciplinary management strategies for high-risk pregnancies in consanguineous settings. This report presents a case of prenatal suspicion and postnatal confirmation of HI, highlighting the diagnostic limitations, obstetric challenges, and genetic implications. By addressing the gaps in prenatal care and raising awareness about carrier screening and reproductive options, gynecologists can play a crucial role in supporting high-risk pregnancies and reducing the recurrence risk in future generations